Automotive mechanics - Ed MAY (McGraw-Hill, 2000)
This book covers engine construction and overhaul, fuel and engine management, automatic transmissions and four-wheel drive, diesel engines, the rotary engine, electrical systems and air conditioning, safety, security and convenience